2021
DOI: 10.3389/fcvm.2021.709169
|View full text |Cite
|
Sign up to set email alerts
|

New Developments in Exosomal lncRNAs in Cardiovascular Diseases

Abstract: Long non-coding RNAs (lncRNAs) are non-coding RNAs with lengths >200 nt and are involved in the occurrence and development of cardiovascular diseases (CVDs). Exosomes are secreted and produced by various cell types. Exosome contents include various ncRNAs, proteins and lipids. Exosomes are also important mediators of intercellular communication. The proportion of lncRNAs in exosomes is low, but increasing evidence suggests that exosomal lncRNAs play important roles in CVDs. We focused on research progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 107 publications
0
18
0
Order By: Relevance
“…On other hand at the post-transcriptional level, they can serve as scaffold for protein post-transcriptional modifications (phosphorylation, protein degradation), multimeric protein complex formation or as competing endogenous RNAs for microRNA sponging [ 73 , 80 , 81 ]. Furthermore, lncRNAs can also be processed to be loaded into extracellular vesicles, such as exosomes, and thus participate in intercellular communication processes [ 83 , 84 ].…”
Section: Biogenesis and Function Of Micrornas And Lncrnasmentioning
confidence: 99%
“…On other hand at the post-transcriptional level, they can serve as scaffold for protein post-transcriptional modifications (phosphorylation, protein degradation), multimeric protein complex formation or as competing endogenous RNAs for microRNA sponging [ 73 , 80 , 81 ]. Furthermore, lncRNAs can also be processed to be loaded into extracellular vesicles, such as exosomes, and thus participate in intercellular communication processes [ 83 , 84 ].…”
Section: Biogenesis and Function Of Micrornas And Lncrnasmentioning
confidence: 99%
“…Hence, lncRNAenriched EVs are readily being reported as biomarkers [54]. The active process of lncRNA sorting into exosomes can be facilitated by RNA-binding proteins (RBPs) with a growing understanding of their mechanism of loading and action involving epigenetic modifications, through which exosomal lncRNAs can alleviate the progression of some diseases [55,56].…”
Section: Long Non-coding Rnas As Remodellers Of the Vascular Epigenomementioning
confidence: 99%
“…The mechanisms behind PRC2 engagement with native chromatin, as well as its recruitment in a context-dependent manner, remain to be fully understood [58]. EZH2mediated epigenomic landscapes guide cardiovascular and endothelial differentiation and maturation, maintain tissue-specific genetic blueprints established during development, and are implicated in cardiovascular disease [55,57,58]. Moreover, PRC2 histone methyltransferase activity appears to be a key regulator of angiogenesis.…”
Section: Polycomb Repressive Complex 2 and Lncrnasmentioning
confidence: 99%
“…Recently, numerous studies have confirmed that stem cells mainly exert their effect on CVDs by inducing the secretion of paracrine factors mainly in exosome (Exo) ( Elshaer et al, 2018 ; Terashvili and Bosnjak, 2019 ; Wu et al, 2020 ). Although the proportion of long non-coding RNAs (lncRNAs) in Exo is very low ( Huang, 2020 ; Hui et al, 2020 ; Pham and Boon, 2020 ), research shows that lncRNAs, especially in stem cell-derived Exo, contribute significantly to treat CVDs by regulating gene expression at the transcriptional level, acting as a molecular sponge that targets miRNA, interfering with chromatin complexes to repress or activate gene expression in an epigenetic fashion and participating the processes of apoptosis, pyrosis, autophagy, myocardial fibrosis, and angiogenesis ( Li et al, 2018 ; Deng et al, 2019 ; Pan et al, 2019 ; Yan et al, 2020 ; Chen et al, 2021a , 2021a ; Yuan and Huang, 2021 ). For example, mesenchymal stem cells (MSCs)-Exo-lncRNA-FENDRR can be taken up by human vascular endothelial cells (HUV-EC-C), where they activate the TEA domain transcription factor 1 (TEAD1) by targeting microRNA (miR)-28 and, thus, inhibits apoptosis, oxidative stress, and inflammatory response of HUV-EC-C, reducing the accumulation of oxidized low-density lipoprotein (ox-LDL), and reduces the formation of atherosclerotic plaques ( Zhang N. et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%